Decolonising the South African art curriculum - Smith, Candice Jane (My University, 2018)
This study is a broad inquiry into art education and curriculum. This research focuses on determining the modernist ideologies that underpin the Visual art curriculum and assessment policy (CAPS) document for grades 10 to 12 and considers the impact of modernist ideologies on decolonising art curriculum. A content analysis has been used in relation to the available literature, various iterations of the art curriculum and the prescribed CAPS textbooks for Visual art. My argument is that the curriculum does contain modernist underpinnings that hinder the decolonial potential of the CAPS curriculum and will reproduce the underlying modern system. There has been a call for decolonised curriculum across educational institutes and for education that is relevant to the learner's world.
A research report submitted in partial fulfilment to the Degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2018
Keywords: Curriculum evaluation--South Africa; Art--Study and teaching (Secondary)--South Africa; Art--Study and teaching--Curricula